REVIEW: The evolving linkage between conservation science and practice at The Nature Conservancy. Issue 5 (19th May 2014) - Kareiva, Peter; Groves, Craig; Marvier, Michelle; Hulme, Philip
Summary The Nature Conservancy (TNC) was founded by ecologists as a United States land trust to purchase parcels of habitat for the purpose of scientific study. It has evolved into a global organization working in 35 countries 'to conserve the lands and waters on which all life depends'. TNC is now the world's largest conservation non‐governmental organization (NGO), an early adopter of advances in ecological theory and a producer of new science as a result of practising conservation. The Nature Conservancy's initial scientific innovation was the use of distributional data for rare species and ecological communities to systematically target lands for conservation. This innovation later evolved into a more rigorous approach known as 'Conservation by Design' that contained elements of systematic conservation planning, strategic planning and monitoring and evaluation. The next scientific transition at TNC was a move to landscape‐scale projects, motivated by ideas from landscape ecology. Because the scale at which land could be set aside in areas untouched by humans fell far short of the spatial scale demanded by conservation, TNC became involved with best management practices for forestry, grazing, agriculture, hydropower and other land uses. A third scientific innovation at TNC came with the pursuit of multiobjective planning that accounts for economic and resource needs in the same plans that seek to protect biodiversity. The Millennium Ecosystem Assessment prompted TNC to become increasingly concerned with ecosystem services and the material risk to people posed by ecosystem deterioration. Finally, because conservation depends heavily upon negotiation, TNC has recently recruited social scientists, economists and communication experts. One aspect still missing, however, is a solid scientific understanding of thresholds that should be averted. Synthesis and applications. Over its 60‐plus year history, scientific advances have informed The Nature Conservancy (TNC)'s actions and strategies, and in turn the evolving practice of conservation has altered the type of science sought by TNC in order to maximize its conservation effectiveness.